2016
DOI: 10.1371/journal.pone.0146285
|View full text |Cite
|
Sign up to set email alerts
|

Viral Reservoirs in Lymph Nodes of FIV-Infected Progressor and Long-Term Non-Progressor Cats during the Asymptomatic Phase

Abstract: BackgroundExamination of a cohort of cats experimentally infected with feline immunodeficiency virus (FIV) for 5.75 years revealed detectable proviral DNA in peripheral blood mononuclear cells (PBMCs) harvested during the asymptomatic phase, undetectable plasma viral RNA (FIV gag), and rarely detectable cell-associated viral RNA. Despite apparent viral latency in peripheral CD4+ T cells, circulating CD4+ T cell numbers progressively declined in progressor animals. The aim of this study was to explore this dich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(34 citation statements)
references
References 42 publications
2
30
0
2
Order By: Relevance
“…This animal has been characterized as a FIV-infected long-term non-progressor (LTNP) cat. [9,11] Additionally, we have demonstrated methylation and deacetylation of histone proteins physically associated with the FIV-promoter in peripheral blood CD4+ T cells isolated during the asymptomatic phase, which is consistent with a condensed chromatin pattern and viral latency. [12] Recently, we demonstrated evidence of active FIV replication in the popliteal lymph nodes in the face of an apparent absence of active viral replication in peripheral blood.…”
Section: Introductionsupporting
confidence: 70%
“…This animal has been characterized as a FIV-infected long-term non-progressor (LTNP) cat. [9,11] Additionally, we have demonstrated methylation and deacetylation of histone proteins physically associated with the FIV-promoter in peripheral blood CD4+ T cells isolated during the asymptomatic phase, which is consistent with a condensed chromatin pattern and viral latency. [12] Recently, we demonstrated evidence of active FIV replication in the popliteal lymph nodes in the face of an apparent absence of active viral replication in peripheral blood.…”
Section: Introductionsupporting
confidence: 70%
“…Infection of bone marrow cells in naturally infected asymptomatic cats has also been reported, although the identity of infected subsets was not determined [25]. Two recent investigations into tissue reservoirs by our laboratory demonstrated the presence of proviral DNA within the popliteal lymph node, mesenteric lymph node, spleen and mucosa of the small intestines during the late asymptomatic phase of infection (5-6 years post inoculation), in the face of a relatively quiescent or inactive viral harbour replication-competent provirus in spite of relatively quiescent or inactive viral replication in the peripheral blood [79,92,109]. Interestingly, our studies revealed that, firstly, lymph node germinal centres contained an increased frequency of CD3+ T cells compared to uninfected cat tissues.…”
Section: Fiv Tissue Reservoirsmentioning
confidence: 97%
“…Evidence that proviral DNA loads may shift between cellular subsets as disease progresses, especially as CD4+ T cells are depleted, has been presented in a limited number of reports [26,27,79]. The hallmark of FIV infection in the acute and early asymptomatic phases of infection is an inverted peripheral blood CD4:CD8 T cell ratio initially due to a decrease in CD4+ T cells and in some cases a concurrent expansion of CD8+ T cells [60,[80][81][82].…”
Section: Cell Reservoirs Of Fivmentioning
confidence: 99%
See 2 more Smart Citations